Metode dalam Islam dan Implementasinya di SMP Annur Prima - Arlina, Arlina; Azzahra, Dini; As-Salim, Malikul Sholeh; Agustin, Rika Nurmida (AHKAM, 2025)
Learning methods are ways that teachers use to convey learning materials to students in achieving goals. Teachers are also expected to be objective in epistemological aspects and apply holistic and flexible methods, strategies and approaches. Choosing a method must be accurate in accordance with various factors, so that the results will be satisfactory. There are 8 methods of learning in Islam: the method of targib, tarhib, exemplary, story, habituation, tamsil, memorization, warning and giving motivation. The method we use in this research is a phenomenalogical qualitative method by collecting some field data, in the form of observation, interviews and documentation. The results showed that Islamic learning methods at An-nur Prima Junior High School have been implemented in the classes so that learning runs effectively and can also shape the character of students who are more religious.